EFFECTIVENESS OF CULTURALLY BASED DANCE LEARNING MEDIA IN ENHANCING STUDENT MOTIVATION AT JUNIOR HIGH SCHOOLS IN SIDENRENG RAPPANG, INDONESIA - Miftahul Jannah; Henra Setiawan; Imron Burhan (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to design and evaluate the effectiveness of culturally-based dance learning media in enhancing student motivation at UPT SMP Negeri 1 Tellu Limpoe, Sidenreng Rappang Regency. The research employed a Research and Development (R&D) approach, integrating the 4D, ADDIE, and Borg & Gall models with a focus on the Define and Design stages. The learning media was developed based on the traditional Pattennung Dance, presented in the form of an interactive video, and validated by media and content experts. Data were collected through observation, interviews, documentation, and validation instruments. The research findings indicate that the developed media effectively increased students’ enthusiasm, active participation, and understanding of dance learning material. Students responded positively during the learning process, while teachers acknowledged that the media effectively delivered content in an engaging and contextual manner. In conclusion, this culturally-based dance learning media is feasible for use and further development as an innovative and local wisdom-based learning alternative.